Kynurenines and Vitamin B6: Link Between Diabetes and Depression. - Oxenkrug Gregory; Ratner Rebecca; Summergrad Paul (Journal of Bioinformatics And Diabetes, 2013)
The increased association between depression and diabetes mellitus is generally acknowledged. Recent studies suggest that depression leads to diabetes.However, the underlying molecular mechanisms for this association remain unclear.Literature and our data indicate that inflammatory and/or stress factors in depression up-regulate tryptophan (TRP) conversion into kynurenine (KYN), a substrate for nicotinamide adenine dinucleotide (NAD) biosynthesis. Deficiency of vitamin B6, a co-factor of the key enzymes of KYN – NAD pathway, shunts KYN metabolism from formation of NAD towards production of xanthurenic (XA) and kynurenic (KYNA) acids. Human and experimental studies reveal that XA, KYNA and their metabolites interfere with production, release and biological activity of insulin. We propose that inflammation- and/or stress-induced up-regulation of TRP – KYN metabolism in combination with vitamin B6 deficiency is one of the mechanisms mediating increased risk of diabetes in depression. Consequently, monitoring formation of diabetogenic KYN derivatives might help to identify subjects-at-risk for the development of diabetes. Pharmacological down-regulation of the TRP – KYN – NAD pathway and maintenance of adequate vitamin B6 status might help to prevent the development of diabetes in depression and other conditions associated with inflammation/stress–induced excessive production of KYN and vitamin B6 deficiency, e.g., obesity, cardiovascular diseases, aging, menopause, pregnancy, and hepatitis C virus infection.
Keywords: diabetes